Preparation of VOC low-temperature oxidation catalysts with copper and iron binary metal oxides via hydrotalcite-like precursors. Issue 54 (8th December 2022) - Zhang, Hongwei; Li, Jianjun; Shu, Song; Guo, Jiaxiu; Liu, Yongjun; Cen, Wanglai; Li, Xinpeng; Yang, Jianrong
Abstract : Design diagram for the removal toluene by Cu–Fe catalyst prepared from precursor hydrotalcite. Abstract : Catalysts are the key to catalytic combustion which is known as an effective method for VOC treatment of industrial waste gas. However, in a typical catalyst, the efficiency of non-noble catalysts, with well economic, is generally poor at catalytic oxidation of VOC from industrial waste gas. In this work, a non-noble catalyst CuFe-4.5 from Cu–Fe elements combined with the properties of hydrotalcite to successfully be prepared. The difference between hydrotalcite as a precursor catalyst and the traditional method was systematically investigated by XRD, FT-IR, SEM, TG, N2 adsorption–desorption isotherms, H2 -TPR, O2 -TPD, and XPS. By forming the hydrotalcite structure, the structural properties of the derivative oxide catalyst can be optimized and the interaction between Cu and Fe in the system can be strengthened. It is more prone to electrons cycle, has more chemically adsorbed oxygen, facilitates catalyst surface activation and shows better efficiency. The catalyst with high activity for VOC in flue gas at low temperature, with 90% conversion at 236 °C, which is about 60 °C lower than commercial catalysts such as EnviCat® from Clariant, Germany, and also has some advantages over current studies. Our study provides a new perspective on the design of efficient VOC catalysts.